The possible role of hydration in concussions and long-term symptoms of concussion for athletes. A review of the evidence. (July 2020) - Clark, James E; Sirois, Emily
The purpose of this review is to address what is known, speculated, and hypothesized regarding the issue of hydration and concussions. Based on the question, "What impact does hydration have on the relative risk for suffering concussive injuries along with long-term ramifications that have been associated with concussive (and repeated subconcussive) traumas to the cerebral cortex?, " a search of available literature was performed through June 2019. Deducing from the available literature, we can stipulate that changes in hydration within the cerebral cortex increase the likelihood for disruption of neurofilament proteins, dysregulation of membrane dynamics of the neurons and exacerbate inflammation responses following head trauma. As such, it can be speculated that differences in incidence rates may be attributed to difference in tissue fluid based on athlete demographics, level of whole-body water balance, and degree of tissue dehydration more than selection of sport. Moreover, tissue hydration in combination with other inflammation factors provides the scaffolding for the development of long-term issues (e.g. chronic traumatic encephalopathy) associated with repetitive head trauma in athletes.